HIGD2A silencing impairs hepatocellular carcinoma growth via inhibiting mitochondrial function and the MAPK/ERK pathway - Kuiyuan Huang; Ziying Liu; Zhanglian Xie; Xiaoran Li; Haixing Zhang; Yu Chen; Yiran Wang; Zimo Lin; Chuanjiang Li; Hongyan Liu; Xiaoyong Zhang (Journal of Translational Medicine, 2023)
Abstract Background The Hypoxia inducible gene domain family member 2A (HIGD2A) protein is indispensable for the assembly of the mitochondrial respiratory supercomplex, which has been implicated in cell proliferation and cell survival under hypoxic conditions. Because the liver has a naturally low oxygen microenvironment, the role of HIGD2A in the development of hepatocellular carcinoma (HCC) remains largely unknown. Methods Gene expression data and clinical information were obtained from multiple public databases. A lentivirus-mediated gene knockdown approach was conducted to explore the function and mechanism of HIGD2A activity in HCC cells. In vivo and in vitro assays were performed to investigate the biological roles of HIGD2A. Results HIGD2A was overexpressed in HCC tissues and cell lines and was associated with a worse prognosis. Silencing HIGD2A expression significantly attenuated cell proliferation and migration, caused S-phase cell cycle arrest, and decreased tumor formation in nude mice. Mechanistically, HIGD2A depletion greatly decreased cellular ATP levels by disrupting mitochondrial ATP production. Moreover, HIGD2A knockdown cells displayed impaired mitochondrial function, such as mitochondrial fusion, increased expression of the mitochondrial stress response protein, and decreased oxygen consumption. Furthermore, knockdown of HIGD2A markedly attenuated the activation of the MAPK/ERK pathway. Conclusions HIGD2A promoted liver cancer cell growth by fueling mitochondrial ATP synthesis and activating the MAPK/ERK pathway, suggested that targeting HIGD2A may represent a new strategy for HCC therapy.